The relationship between health-promoting behaviors and negative emotions in college freshmen: a cross-lagged analysis - Tao, YunFei; Wu, JinLong; Huang, Li; Zheng, KangYong; Liu, HaoWei; Tian, HaoDong; Peng, Li (Frontiers in Public Health, 2024)
Background: The incidence of mental health problems among college students is on the rise. Enhancing mental health may be possible through behavioral modifications and psychological interventions.Objective: This study seeks to explore the link between health-promoting behaviors and negative emotions in college freshmen and assess how different aspects of these behaviors, along with other variables, influence the levels of stress, anxiety, and depression in this group.Methods: Using the Negative Emotion and Health-Promoting Behavior scales, a seven-month longitudinal study was conducted on 4,252 college freshmen, with two data collection points (T1: November 12, 2021, and T2: June 17, 2022). Out of these, 3,632 valid samples were obtained. The study aimed to explore the association and impact between negative emotions and the level of health-promoting behaviors among college students during their time at the university. Results: ①There were significant differences in the levels of health-promoting behaviors and negative emotions over the course of 7 months (P < 0.05). Health-promoting behaviors were found to have a significant negative correlation with negative emotions (P < 0.05). ②Negative emotions at T1 significantly negatively predicted health-promoting behaviors at T2 (β= -0.11, P < 0.01), while health-promoting behaviors at T1 significantly negatively predicted negative emotions at T2 (β= -0.12, P < 0.001). ③Stress management (β= -0.104, P < 0.05; β= -0.087, P < 0.05), self-actualization (β= -0.282, P < 0.01; β= -0.260, P < 0.05), health responsibility (β= -0.057, P < 0.05; β= -0.088, P < 0.05), and interpersonal relations (β = 0.068, P < 0.01; β= 0.138, P < 0.05) were important components in improving stress and anxiety. Self-actualization (β= -0.437, P < 0.001), exercise (β= 0.048, P < 0.001), nutrition (β= 0.044, P < 0.001), and interpersonal relations (β= 0.065, P < 0.001) were important components in improving depression. ④Gender, place of household registration, and whether the individual is an only child were significant factors affecting negative emotions in college freshmen. Conclusion: Health-promoting behaviors significantly impact the emotional well-being of college freshmen, with improvements in these behaviors potentially reducing negative emotions. Notably, gender, household location, and only-child status also affect these emotional states.